2022
DOI: 10.3138/cpp.2022-003
|View full text |Cite
|
Sign up to set email alerts
|

New Canadians Working amid a New Normal: Recent Immigrant Wage Penalties in Canada during the COVID-19 Pandemic

Abstract: The global COVID-19 pandemic has exposed and arguably intensified many existing inequalities. The present analysis explores the relationship between recent immigrant earnings and the pandemic. Specifically, we attempt to empirically answer the question: Has the COVID-19 pandemic exacerbated (mitigated) recent immigrant-non-immigrant employment and wage gaps? We find that the pandemic did not change the labour force activity profile of recent nor long-term immigrants. Furthermore, the pandemic did not dispropor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Accordingly, the workers in the bottom quartile of weekly earnings comprised more than one-half of job losses, and workers paid hourly (as opposed to salaried), younger workers and non-union workers lost the most work. Furthermore, as Lamb et al (2022) states, the labour market realities facing many recent immigrants before the pandemic were already quite precarious.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the workers in the bottom quartile of weekly earnings comprised more than one-half of job losses, and workers paid hourly (as opposed to salaried), younger workers and non-union workers lost the most work. Furthermore, as Lamb et al (2022) states, the labour market realities facing many recent immigrants before the pandemic were already quite precarious.…”
Section: Resultsmentioning
confidence: 99%
“…Research has found that the COVID-19 pandemic compounded existing inequalities in the Canadian labour market. For example, Hou et al (2020) found that racialized individuals suffered greater financial insecurity (compared to the White population) because they were more likely to have precarious and lower-paying jobs, experience job loss or decreased hours of employment (see also, Mo et al 2020). Lamb et al (2022 found that recent immigrants were more likely than Canadian-born workers to be unemployed, irrespective of the pandemic (p. 71).…”
Section: Impact Of Covid-19 On Job Outcomes Of Racialized Immigrantsmentioning
confidence: 99%